2015
DOI: 10.3892/mmr.2015.3648
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of polysaccharide extracted from Pleurotus ostreatus mycelia against gastric cancer in vitro and in vivo

Abstract: The present study aimed to determine the antitumor effects of polysaccharides extracted from Pleurotus ostreatus mycelium on gastric cancer in vitro and in vivo. Polysaccharides were extracted from Pleurotus ostreatus mycelium and an antitumor component, known as Pleurotus ostreatus mycelium polysaccharides 2 (POMP2), with a relative molecular weight of 29 kDa, was then sequentially purified using Sephadex G200 size-exclusion chromatography and diethylaminoethyl-52 cellulose ion-exchange chromatography. The MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Furthermore, PSP extract was cytotoxic in the human liver cancer cell line HepG2. These results are consistent with those of [ 32 ] in human colorectal and leukaemia cell lines, with [ 33 ] against gastric cancer in vitro and in vivo , and with [ 34 ] in HepG2, HCT 116 and HeLa cell lines. Additionally, previous reports demonstrated that extracts from P. ostreatus suppressed proliferation of breast cancer (MCF-7, MDA-MB-231) and colon cancer (HT-29, HCT-116) cells, without affecting proliferation of epithelial mammary MCF-10A and normal colon FHC cells [ 5 ].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, PSP extract was cytotoxic in the human liver cancer cell line HepG2. These results are consistent with those of [ 32 ] in human colorectal and leukaemia cell lines, with [ 33 ] against gastric cancer in vitro and in vivo , and with [ 34 ] in HepG2, HCT 116 and HeLa cell lines. Additionally, previous reports demonstrated that extracts from P. ostreatus suppressed proliferation of breast cancer (MCF-7, MDA-MB-231) and colon cancer (HT-29, HCT-116) cells, without affecting proliferation of epithelial mammary MCF-10A and normal colon FHC cells [ 5 ].…”
Section: Discussionsupporting
confidence: 89%
“…The vast literature (more than 1600 citations in the PubMed) on the isolation, structural elucidation, and bioactivities of mushroom polysaccharides includes reports on the following additional mushroom cultivars: Agaricus blazei [ 35 ], Agaricus brasiliensis [ 36 ], Amanita ponderosa [ 37 ], oyster mushroom [ 38 ], Auricularia polytricha [ 39 ], Boletus edulis [ 40 ], Cookeina tricholoma [ 41 ], Cordyceps militaris [ 42 ], Entoloma lividoalbum [ 43 ], Gleoestereum incarnatum [ 44 ], Ganoderma lucidum [ 45 ], Grifola frondosa [ 46 , 47 ], Hohenbuehelia serotina [ 48 ], Hypsizygus marmoreus [ 49 ], Iliodiction cibarium [ 50 , 51 ], Lactarius deliciosus [ 52 ], Lentinus edodes [ 31 , 53 ], Macrolepiota dolichaula [ 54 ], Phellinus igniarius [ 55 ], Phellinus linteus [ 56 ], Phellinus pini [ 57 ], Pholiota adiposa [ 58 ], Pholiota nameko [ 59 ], Pleurotus eryngii [ 60 ], Pleurotus ostreatus [ 55 , 61 ], Termitomyces heimii [ 62 ], Tricholoma matsutake [ 63 , 64 , 65 ], Tricholoma mongolicum [ 66 ]. A journal reviewer noted that it is, however, important to determine if the isolated polysaccharides contain polyphenolic or other bioactive compounds that might affect their activities.…”
Section: Isolation and Characterization Of Mushroom Polysaccharidementioning
confidence: 99%
“…Pleurotus is a large group of mushrooms with high nutritional value and therapeutic properties, as well as a wide range of biotechnological and environmental applications (Knop, Yarden, & Hadar, ). P. ostreatus polysaccharides possess antioxidant, anticancer, and antitumor properties (Cao, Liu, Yang, Hou, & Li, ; Uddin Pk et al, ). The differences in physicochemical and structural properties including molecular weights, monosaccharide compositions, glycosidic bonds, and chain conformation of the polysaccharides are known to affect the pharmacological activities of polysaccharides.…”
Section: Introductionmentioning
confidence: 99%